2013
DOI: 10.3389/fnins.2013.00116
|View full text |Cite
|
Sign up to set email alerts
|

A simple solution for model comparison in bold imaging: the special case of reward prediction error and reward outcomes

Abstract: Conventional neuroimaging techniques provide information about condition-related changes of the BOLD (blood-oxygen-level dependent) signal, indicating only where and when the underlying cognitive processes occur. Recently, with the help of a new approach called “model-based” functional neuroimaging (fMRI), researchers are able to visualize changes in the internal variables of a time varying learning process, such as the reward prediction error or the predicted reward value of a conditional stimulus. However, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…R. Roesch et al, 2010), although medial OFC activation has been shown to be coupled to RPE in some human fMRI studies. Our findings are consistent with the view that this is likely to be due to the correlation inherent between appetitive properties of the outcome and RPE in many of these designs (Erdeniz, Rohe, Done, & Seidler, 2013; Rohe et al, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…R. Roesch et al, 2010), although medial OFC activation has been shown to be coupled to RPE in some human fMRI studies. Our findings are consistent with the view that this is likely to be due to the correlation inherent between appetitive properties of the outcome and RPE in many of these designs (Erdeniz, Rohe, Done, & Seidler, 2013; Rohe et al, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…For this reason, three reduced general linear models were estimated and compared for each participant to decide, for each voxel separately, whether its BOLD response was overall better predicted by a model assuming activation only during visuomotor planning, only during online visuomotor processing or throughout both trial phases [ 50 ]. Each model comprised both sessions of the virtual avatar control task, high pass filtered with a high pass cut off at 128s to remove low frequency drifts, and an autoregressive model AR(1) to account for serial autocorrelations in the time series.…”
Section: Methodsmentioning
confidence: 99%
“…The three models were voxel-wise compared to reduce the risk of misattributing activation to a movement phase that contributed only little to the observed blood oxygen level dependent (BOLD) time-course. For each voxel and participant, we assessed whether log residual variance (ImCalc function of SPM) was smallest (greater model fit, more explained variance in the BOLD signal time-course) for the planning, online processing or combined model [ 50 ]. Afterwards, voxels whose BOLD signal changes were better described by the planning relative to the online processing and combined model (Planning log(residualVariance) < Execution log(residualVariance) ∩ Planning log(residualVariance) < Control log(residualVariance) , p < 0.05, uncorrected) were collected in a mask that was used for subsequent statistical interference in the planning model.…”
Section: Methodsmentioning
confidence: 99%
“…To account for the potential impact of the electrotactile stimulation on neural activity, the design matrix also included a "shock" regressor. Because PE and the occurrence of the shock are highly correlated (Erdeniz, Rohe, Done, & Seidler, 2013), PE-related neural activity was not interpreted. Beta coefficients for the onset phase modulated by V and the outcome phase modulated by dB were included in the second-level analyses.…”
Section: Voxelwise Analysesmentioning
confidence: 99%